2014
DOI: 10.1590/1807-1929/agriambi.v18n09p971-979
|View full text |Cite
|
Sign up to set email alerts
|

Características químicas de substratos formulados com lodo de esgoto para produção de mudas florestais

Abstract: Objetivou-se, com o trabalho, caracterizar as propriedades químicas e as composições dos substratos formulados à base de lodo de esgoto em diferentes combinações com resíduos orgânicos e vermiculita, a fim de se obter um meio de crescimento adequado para o crescimento de mudas florestais. Foi realizada análise de teores totais e disponíveis dos nutrientes dos 26 substratos formulados a partir da mistura de lodo de esgoto com vermiculita e os resíduos fibra de coco, palha de café in natura, composto orgânico, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 12 publications
(11 reference statements)
3
17
0
16
Order By: Relevance
“…Mean values of phosphorus (P), organic matter (OM), hydrogen potential (pH), potassium (K + ), calcium (Ca 2+ ), magnesium (Mg 2+ ), potential acidity (H+Al), aluminum (Al 3+ ), F probability and coefficient of variation (CV) for the soil under different doses of agro-industrial (AR) and organic (OR) residues With small variation, Mg +2 had its behavior influenced by both residues (AR and OR), whose highest contents in the soil occurred at the highest doses of both residues ( Figure 2A). These results are consistent with those of Santos et al (2014), who reported beneficial effects on the supply of Mg +2 to the substrate as higher proportions of organic residues were added.…”
Section: +supporting
confidence: 92%
“…Mean values of phosphorus (P), organic matter (OM), hydrogen potential (pH), potassium (K + ), calcium (Ca 2+ ), magnesium (Mg 2+ ), potential acidity (H+Al), aluminum (Al 3+ ), F probability and coefficient of variation (CV) for the soil under different doses of agro-industrial (AR) and organic (OR) residues With small variation, Mg +2 had its behavior influenced by both residues (AR and OR), whose highest contents in the soil occurred at the highest doses of both residues ( Figure 2A). These results are consistent with those of Santos et al (2014), who reported beneficial effects on the supply of Mg +2 to the substrate as higher proportions of organic residues were added.…”
Section: +supporting
confidence: 92%
“…The values in Table 1 and several previous studies (COSTA et al, 2008;SOUSA NETO et al, 2012;RIBEIRO et al, 2012;SANTOS et al, 2014) showed that the sludge is a rich chemical and organic source and can be exploited for different uses. According to Resolution No.…”
Section: Chemical Sludge Analysissupporting
confidence: 52%
“…Santos et al (2014) (SANTOS et al, 2014), podendo ser o maior crescimento aéreo e radicular das mudas de Lafoensia glyptocarpa atribuído à tal riqueza nutricional, refletindo em maior AF, MSPA e MSSR (Tabela 2).…”
Section: Discussionunclassified
“…Assim, a destinação agrícola e florestal do lodo se destaca, devido a riqueza nutricional, alto teor de matéria orgânica e elevada retenção de água, características de grande interesse agrícola SANTOS et al, 2014;NOBREGA et al, 2017).…”
unclassified